2012
DOI: 10.5468/kjog.2012.55.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic review of extrapelvic endometriosis

Abstract: Objective To evaluate the clinicopathologic features of extrapelvic endometriosis in order to help diagnosis and treatment. Methods Thirty patients with extrapelvic endometriosis were surgically diagnosed at Pusan National University Hospital from January 1998 to December 2010. We retrospectively reviewed the medical records such as age, symptoms, preoperative diagnosis, past surgical history. Results There were 30 patients who were diagnosed extrapelvic endometriosis surgically with a mean age of 38 years. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Scar site endometriosis has been reported to occur in approximately 0.03% to 0.4% of women undergoing caesarean section [ 6 ]. A previous study reported the occurrence of endometriosis at the site of a previous operation scar in Korean women [ 7 ]. Fifteen of 30 women with extra-pelvic endometriosis showed endometriotic lesions at the site of a previous cesarean scar.…”
Section: Discussionmentioning
confidence: 99%
“…Scar site endometriosis has been reported to occur in approximately 0.03% to 0.4% of women undergoing caesarean section [ 6 ]. A previous study reported the occurrence of endometriosis at the site of a previous operation scar in Korean women [ 7 ]. Fifteen of 30 women with extra-pelvic endometriosis showed endometriotic lesions at the site of a previous cesarean scar.…”
Section: Discussionmentioning
confidence: 99%
“…The composites have more fine pores, increasing the chance to interfere with the sound wave. This improves the resistance through the vibration of air by means of frictional viscosity . For PU foam, almost all the pores are interconnected between each other. On addition of RH into PU foam, the connected pores are blocked.…”
Section: Resultsmentioning
confidence: 99%
“…This study aimed to investigate the relationship between CHHF and ED in young Taiwanese men. CHHF occurs in about 20–52% of the Eastern Asian population, particularly in women 16 , 17 . The prevalence of CHHF in men has been reported to be approximately 10.4–44.3% 5 , 6 , 10 , 15 , 18 , which is comparable to the 27.9% incidence found in our study.…”
Section: Discussionmentioning
confidence: 99%